FAWZIYA Examining Key Success Factors for Effective Risk Management Affecting Bank Muscat’s Financial Performance: Case of Oman.: Risk Management Affecting Bank Muscat’s Financial Performance: - AL-JABRI, FAWZIYA (Advances in Social Sciences Research Journal, 2021)
Risk Management is considered as one of the major bank’s financial performance case of Oman. In recent years, the administration and financial corruptions has been shown to affect the financial performance of banks. Therefore, it provides rapid analysis to identify and examine those key factors and come up with better framework for more effective risk management of bank’s financial performance. As project topic shown, the aim of the study is to determine key success factors and the influence of risk management to banks financial performance. However, risk management has adverse effects. The project provides literature review from scholarly sources for examining the positive impact of risk management. The project carries primary and secondary data to obtain the information of research. The finding of the project indicates to be more effective in banks financial performance. In addition, risk management should ensure the banks financial performance and controlling with success in business through financial planning and control. Finally, contribution of the project could be using as reference source. Many researchers are taken the benefit of the project especially in banks case of Oman. Keywords: Key Success Factors, Risk Management, Bank Financial Performance, Effective